Institutional Record of the Clinical Ethics Service of Hospital Universitario San Ignacio (HUSI): An Analysis of its Implementation and the Pre‑Pandemic Period (Revista Iberoamericana de Bioética, 2026)
This publication presents the implementation of the institutional registry of the Clinical Ethics Service and offers an analysis of the first data obtained during the pre-pandemic period, from the creation of the SEC in 2015 to the beginning of the pandemic in March 2020.
Keywords: clinical ethics; registry; ethical dilemma; specialized medicine